Combined spiroergometry and 31P–MRS of human calf muscle during high‐intensity exercise. (24th March 2017) - Moll, K.; Gussew, A.; Hein, C.; Stutzig, N.; Reichenbach, J.R.
Abstract : Simultaneous measurements of pulmonary oxygen consumption ( V O2 ), carbon dioxide exhalation ( V CO2 ) and phosphorus magnetic resonance spectroscopy ( 31 P–MRS) are valuable in physiological studies to evaluate muscle metabolism during specific loads. Therefore, the aim of this study was to adapt a commercially available spirometric device to enable measurements of V O2 and V CO2 whilst simultaneously performing 31 P–MRS at 3 T. Volunteers performed intense plantar flexion of their right calf muscle inside the MR scanner against a pneumatic MR‐compatible pedal ergometer. The use of a non‐magnetic pneumotachograph and extension of the sampling line from 3 m to 5 m to place the spirometric device outside the MR scanner room did not affect adversely the measurements of V O2 and V CO2 . Response and delay times increased, on average, by at most 0.05 s and 0.79 s, respectively. Overall, we were able to demonstrate a feasible ventilation response ( V O2 = 1.05 ± 0.31 L/min; V CO2 = 1.11 ± 0.33 L/min) during the exercise of a single calf muscle, as well as a good correlation between local energy metabolism and muscular acidification ( τ PCr fast and pH; R 2 = 0.73, p < 0.005) and global respiration ( τ PCr fast and V O2 ; R 2 = 0.55, p = 0.01). This provides improved insights into aerobic and anaerobic energy supply during strong muscular performances. Abstract : A non‐magnetic pneumotachograph and extension of the sampling line from 3 m to 5 m to place the spirometric device outside the MR scanner room did not affect adversely the measurements of V O2 and V CO2 . We were able to successfully demonstrate the functionality of a spirometric system in combination with an MR scanner to perform simultaneous measurements of V O2, V CO2 and 31 P–MRS in exercising subjects.